Community participation: a pragmatic solution to negative impacts of Covid-19 on household's socioeconomic lives - John Lola Okunola; Sunday Olutayo Fakunle (Insights into Regional Development)
The worldwide outbreak of COVID-19 and its impacts have become an academic concern. The concern has generated a plethora of studies and reports that have identified a number of negative impacts of COVID-19 on household socioeconomic lives in Nigeria. Therefore, Nigerian governments at different levels in conjunction with several international organisations have tried to deal with these impacts; however, the expected result is far below the reality. Advocacy of adopting bottom-top approaches to solving various community problems and the grand relevance of Community-Based Organisations (CBOs), as a form of community participation, prompted this study. The specific objective of the study was to investigate the roles of CBOs in complementing the governments’ efforts to alleviate the negative impacts on household socioeconomic lives. The location of the study was Ife-East Local Government Area of Osun State, Nigeria where there existed a number of various CBOs as in other part of the country. The study was cross-sectional and exploratory in nature while a qualitative method, in-depth face-to-face interview, was employed to collect the primary data for this study. The study covered all the 10 electoral wards that exist in the study location. Via purposive sampling method, 5 CBOs were selected in each of the 10 wards, making a total size of 50 CBOs. To obtain the primary data, 2 CBO leaders (a man and a woman) and 4 CBO members (2 men and 2 women) among the 5 selected CBOs in each of the wards were purposively selected, making a total sample size of 60 from all the electoral wards for the in-depths face-to-face interview. Both thematic and contents analyses were utilized to analyze the collected data. The study found that the CBOs rendered economic support in forms of pooling resources together for fund provision, purchasing goods in large quantities at lower prices, creating platforms to attract loans, assistance and to invite experts for empowerment programmes for their members. The study further found that the CBO members benefited social support in form of provision of platforms to share their experiences, to boost members’ morale to avert psychological challenges that tended to generate committing suicide and to invite medical experts on sensitization programmes about COVID-19 and its effects. As this study solely focused on ways that several aspects of households’ socioeconomic lives were shielded from the negative impacts of the pandemic through community participation via various CBOs, this study solicited future studies that shall focus mainly on the challenges that the CBOs encounter in realizing this goal and the means of coping with the highlighted challenges.